PENINGKATAN HASIL BELAJAR PADA MATERI BANGUN DATAR MENGGUNAKAN STRATEGI PERMAINAN TRADISIONAL ENGKLEK SISWA KELAS IV SDN 105340 DENAI SARANG BURUNG - Selamet Gea; Leni Malinda (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2020)
This researcher has the following objectives: 1) To find out the application of traditional game strategies in order to improve learning outcomes of flat wake material for fourth grade students of SDN 105340 Denai Sarang Burung. 2) To find out the improvement in student learning outcomes after the application of the traditional game strategy of flat-building material in class IV SDN 105340 Denai Denai Sarang Burung. This research is a Classroom Action Research conducted over two cycles consisting of planning, action, observation, and reflection stages. The subjects of this study were fourth grade students of SD Negeri 105340 Denai Sarang Burung with 12 male students and 13 female students. The research uses traditional game strategies. The data collection technique in this study was a test question and was supported by observation and interviews. This test was conducted three times, namely, pre-action test, cycle I test, and cycle II test. Based on the results, the average value of all students obtained from the initial condition research was 60 (low) then increased in the first cycle to 70 (moderate), and increased again in the second cycle to 84 (high). The percentage of student results in the initial conditions was 44% (11 students). Then after being given action, student learning outcomes in the first cycle showed an increase of 64% (16 students). Meanwhile, in the second cycle, the students' learning outcomes were 88% (22 students). From the results of this study, it can be concluded that the application of the traditional engklek game strategy can improve student learning outcomes in grade IV SD Negeri 105340 Denai Sarang Burung